(untitled) (Journal of Computational Mathematics, 1987)
We consider in this note how the principal angles between column spaces R(A) and R(B) change when the elements in A and B are subject to perturbations. The basic idea in the proof of our results is that the non-zero cosine values of the principal angles between R(A) and R(B) coincide with the non-zero singular values of P_AP_B, the product of two orthogonal projections, and consequently we can apply a perturbation theorem of orthogonal projections proved by the author[4].